EMERGING POWER RIVALRY: ANALYZING SHIFTS IN SINO-INDIAN POLICY TOWARDS THE SOUTH ASIAN REGION - Datta, Sujit Kumar (Spektrum, 2025)
This article delves into the evolving power dynamics between China and India in the South Asian region, aiming to scrutinize how their respective policies have shifted in response to emerging geopolitical rivalries. The research objective is to dissect the strategic maneuvers and policy adaptations of both nations, with a focus on understanding the implications for regional stability and power balance. Key research questions include: How have Sino-Indian relations evolved in the context of South Asian geopolitics? What are the primary drivers of their policy shifts? How do these shifts affect the smaller South Asian states? Through a comprehensive analysis of policy documents, diplomatic exchanges, and strategic initiatives, the research finds that both China and India are increasingly asserting their influence through economic investments, military presence, and diplomatic engagements. China’s Belt and Road Initiative (BRI) and India’s Act East Policy are pivotal to their regional strategies. The research argues that while these policies aim to bolster their respective spheres of influence, they also exacerbate tensions and competition, thereby impacting regional alliances and economic development. The findings underscore a nuanced power rivalry where economic diplomacy, infrastructural projects, and security concerns intersect, revealing a complex interplay of cooperation and contention. This rivalry not only reshapes bilateral relations between China and India but also significantly affects the geopolitical landscape of South Asia, necessitating a reevaluation of existing regional policies and alliances.